Particle Size Distribution of Copper Mine Tailings from Lohan Ranau Sabah and its Relationship with Heavy Metal Content - Jopony, Marcus; Usup, Gires; Mohamed, Murtedza (1987)
Particle size analyses were carried out on copper mine tailings from Lohan, Ranau Sabah. About 99.64% of the tailing particles were < 1000 /lm in size while 52.23%,15.72% and 4.87% were < 125 j.l.m, < 62.5 pm and < 38 j.l.m/respectively. The amount of heavy metal extracted by 0.5 HCI was in the order Mn > Cu > Ni > Zn > Co > Cd and is relatively higher in the finer tailing particles.